2019
DOI: 10.2147/idr.s194740
|View full text |Cite
|
Sign up to set email alerts
|

<p>First investigation of the presence of <em>SPATE</em> genes in <em>Shigella</em> species isolated from children with diarrhea infection in Ahvaz, southwest Iran</p>

Abstract: Background: SPATE (serine protease autotransporters of enterobacteriaceae) genes are considered as a group of the main virulence factors of Shigella species This study aimed to investigate for the first time the distribution of SPATE genes among Shigella spp. isolated from children with diarrhea infection in Ahvaz, Iran. Methodology: In this study, a total of 74 Shigella i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(53 reference statements)
5
6
0
Order By: Relevance
“…For example, a study in China reported a higher prevalence of S. flexneri in males than in females; however, S. sonnei showed a reverse trend [ 40 ]. However, in the present study, most isolates were retrieved from male patients in the age group 12–45 years (30/34, 88.2% of isolates), similar to reports by another study in Iran [ 41 ]. The affected age group and gender are important for the epidemiology of shigellosis infections and appeared to be associated with the level of personal hygiene [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…For example, a study in China reported a higher prevalence of S. flexneri in males than in females; however, S. sonnei showed a reverse trend [ 40 ]. However, in the present study, most isolates were retrieved from male patients in the age group 12–45 years (30/34, 88.2% of isolates), similar to reports by another study in Iran [ 41 ]. The affected age group and gender are important for the epidemiology of shigellosis infections and appeared to be associated with the level of personal hygiene [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…A majority of S. flexneri (92.8%) and all of S. sonnei were resistant to SXT, a finding which was similar to those reported by other groups in Iran 15,17,18 and in other countries 19,20 and opposite to that reported by Moosavian et al in Iran. 15 Moreover, in the current study S. flexneri showed high resistance to AMP that is consistent with those previously reported by Iranian authors. 16,21,22 Moreover, a high-level resistance was observed against AMP, NA, MN, CTX, CFM, and AZT among Shigella isolates.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, the serotyping findings indicated that S. sonnei was the most predominant species, which is consistent with the findings reported by Yaghoubi et al 14 in Tehran, Iran. However, Moosavian et al in Ahvaz 15 and Hosseini et al in Kerman 16 previously reported that S. flexneri was the most common species. These variations could be due to the differences between these studies in terms of geographical and socioeconomic conditions as well as the groups of individuals studied.…”
Section: Discussionmentioning
confidence: 95%
“… 32 In this study, most of the S. flexneri isolates harbored two or more SPATE genes, which is consistent with the results of previous studies. 33 , 34 We also found that the sat gene was the most commonly identified SPATE gene among the S. flexneri isolates, but was absent among the S. sonnei isolates. This indicated that sat -encoded toxin might be a major contributor to the virulence of S. flexneri isolates.…”
Section: Discussionmentioning
confidence: 58%